When the gods are angry: volcanic crisis and eruption at Bali's great volcano. (6th April 2018) - Gertisser, R.; Deegan, F.M.; Troll, V.R.; Preece, K.
Abstract : In November 2017, Bali's 'great volcano', Gunung Agung, erupted for the first time since 1963—leading to the evacuation of nearly 150 000 people from a preliminary danger zone within a radius of 9–12 km from the summit. Since the phreatic onset of the eruption on 21 November, intermittent magmatic (Vulcanian) explosions continued to threaten local residents and disrupt air traffic to and from Indonesia's favourite tourist destination. Whereas the opening of the eruption seems to have been less energetic than the opening of the 1963 events, as of January 2018, the volcanic Alert Level for Agung remains at the highest level. Indeed, it remains unclear at this point what course the eruption will take and how long it will last, and the possibility remains that the eruption may turn more energetic in the months to come.